Non-covalent interactions of pyrene end-labeled star poly(-caprolactone)s with fullerene - Uner, Ahmet; Doganci, Erdinc; Tasdelen, M. Atilla (Wiley, 2018)
Pyrene end-labeled star poly(-caprolactone)s (PCLs) with polyhedral oligomeric silsesquioxane (POSS) core were prepared by combination of copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click chemistry and ring-opening polymerization techniques. First, -caprolactone (-CL) is polymerized by using 1-pyrene methanol as initiator and stannous octoate as catalyst to obtain -pyrene--hydroxyl telechelic PCL with different chain lengths. Then, its hydroxyl group is converted to acetylene functionality by esterification reaction with propargyl chloroformate. Finally, the CuAAC click reaction of -pyrene--acetylene telechelic PCL with POSS-(N-3)(8) leads to corresponding pyrene end-labeled star-shaped PCLs. The successful synthesis of pyrene end-labeled star polymers is clearly confirmed by H-1-nuclear magnetic resonance, Fourier transform infrared, gel permeation chromatograph, differential scanning calorimeter, and thermogravimetric analysis. Furthermore, non-covalent interactions of obtained star polymers with fullerene are investigated in liquid media. Based on Raman spectroscopy and visual investigations, the star polymer having shorter chain length exhibited better and more stable dispersion with fullerene. The amount of pyrene units present per polymer chains can directly influence the dispersion stability of fullerene. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46520.
Keywords: functionalization of polymers; graphene and fullerenes; nanotubes; surfaces and interfaces